2021
DOI: 10.3221/igf-esis.56.01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the survivability of CFRP honeycomb-cored panels in compression after impact tests

Abstract: This paper is oriented to the experimental research of the mechanics of the CFRP sandwich plates, glass and carbon fiber sample panels with a large-cell honeycomb core. The method for testing polymer composite sample plates in compression after impact (CAI) tests with joint use of a testing machine and a video system for deformation field registration was tested. Analysis of the experimental data obtained highlighted the impactive sensitivity zone for the test specimens. A quantitative assessment of the load-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…The findings of this study showed that the design process was reliable and the safety of CRSCs is considered; however, the probability failure for mid-rise CRSCs was more than low-rise prototypes [21]. Apart from the above mentioned studies, very little attention has been paid to experimental researches for understanding the structural behavior of buildings against vehicles collision due to its setup and an expensive procedure [22,23]. Therefore, this is a major reason for developing the analytical models based on probabilistic approaches to perceive the performance of buildings under vehicle impact.…”
Section: Introductionmentioning
confidence: 90%
“…The findings of this study showed that the design process was reliable and the safety of CRSCs is considered; however, the probability failure for mid-rise CRSCs was more than low-rise prototypes [21]. Apart from the above mentioned studies, very little attention has been paid to experimental researches for understanding the structural behavior of buildings against vehicles collision due to its setup and an expensive procedure [22,23]. Therefore, this is a major reason for developing the analytical models based on probabilistic approaches to perceive the performance of buildings under vehicle impact.…”
Section: Introductionmentioning
confidence: 90%
“…, 2003; Staroverov et al. , 2019, 2021). However, it is difficult to detect new defects by visual examination without specialised equipment.…”
Section: Introductionmentioning
confidence: 99%
“…These types of loads cause interlayer cracking of material structure, which may eventually lead to delamination and decreased performance of structures made of composite materials (Cantwell and Morton, 1991;Kang et al, 2005;Feng et al, 2017;Bogenfeld et al, 2020). For these load types, the main study methods are local impact tests using a falling ball weight, as well as compression tests after the impact to assess the residual strength of composite laminates (Tai et al, 1998;Suh et al, 2003;Staroverov et al, 2019Staroverov et al, , 2021. However, it is difficult to detect new defects by visual examination without specialised equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the research on impact damage characteristics of composites by domestic and foreign scholars mostly focused on the vertical impact on the center of the composite panels [9][10][11][12][13][14][15][16]. However, research on the edge impact properties of composite laminates was rare until 2008, when Malhotra [17] proposed the idea that composites near special locations such as the edges of aircraft wings, inspection ports or the edges of other holes in the aircraft are highly susceptible to edge impact from foreign objects, that scholars gradually began to investigate the edge impact and compression after edge impact performances of composites.…”
Section: Introductionmentioning
confidence: 99%